Volunteering in Disaster Management for Development in Africa: Reflections from Bukoba District, Tanzania (Tanzania Journal for Population studies and Development, 2024)
Volunteering is an old phenomenon; but it never gets obsolete. It plays a pivotal role in disaster management and development, particularly in resource-constrained settings. This article explores the critical contributions of community volunteers during the 2016 earthquake in Bukoba, Tanzania; highlighting their agency in handling the crisis. Drawing on the social construction of reality theory, this article examines how volunteers externalize their intentions, objectify their roles, and internalize their experiences to create a resilient community response that fills institutional gaps. The paper draws from a qualitative study that applied key informant interviews, focus group discussions, participant observation, and documentary review to unearth the lived experiences of earthquake survivors’ interaction with community volunteers. Findings reveal that volunteers provided immediate rescue and medical assistance; including quick excavation and transfer of casualties to health facilities, navigated bureaucratic challenges, and fostered community resilience and economic recovery. The article underscores the need for integrating volunteer efforts into formal disaster management frameworks to enhance effectiveness and sustainability, especially in disaster-prone settings and poor neighbourhoods. The article concludes that by recognizing the diverse contributions of volunteers, both formal institutions and community initiatives can better address disaster risks and promote development outcomes.